"Pseudomyxoma Endometrii": Endometrial Deposition of Acellular Mucin from a Low-Grade Appendiceal Mucinous Neoplasm as a Rare Mimic of Myxoid Uterine Tumors. (July 2015) - Shaw, Kristin C.; Kokh, Dina; Ioffe, Olga B.; Staats, Paul N.
Abstract : Low-grade appendiceal mucinous neoplasms (LAMNs) are commonly associated with deposition of mucin, with or without admixed low-grade epithelium, on peritoneal surfaces (pseudomyxoma peritonei). We describe a very rare presentation of LAMN as extensive mucin deposition in the endometrium of a 43-yr-old woman initially mistaken for a primary uterine myxoid neoplasm. The patient underwent endometrial curettage that demonstrated abundant myxoid/mucoid material interspersed with small vessels, bland eosinophilic spindled cells, scattered foci of typical endometrial stroma, and occasional endometrioid glands. The endometrial stroma was positive for CD10, and the eosinophilic spindled cells were positive for actin. The lesion was interpreted as "myxoid/mucinous neoplasm, most likely of smooth muscle/endometrial stromal origin." Subsequent laparotomy revealed peritoneal mucin in the anterior cul-de-sac and a dilated appendix. Pathologic review confirmed appendiceal LAMN and multifocal peritoneal mucinosis. The uterus contained scant residual mucoid material. On review of all pathologic material at our institution, the endometrial lesion was consistent with organizing mucin derived from the LAMN with entrapped benign endometrium. "Pseudomyxoma endometrii" is readily mistaken for a primary uterine myxoid neoplasm, particularly myxoid endometrial stromal tumor. A key to diagnosis is recognition that the material is mucin rather than myxoid stroma. This is evidenced by the absence of embedded stromal cells and presence of myofibroblastic, vascular, and macrophage infiltration associated with organization. Epithelium containing goblet cells is an important clue if present. The presence of rare endometrial glands within the endometrial stroma suggests that the latter is entrapped rather than neoplastic.